Social skills at work - "Fontana, David" (London, 1990)
This book goes beyond the dos and don'ts of a mechanical set of skills to provide thoughtful and practical guidelines on the effective management of professional relationships. Exercises and case studies are used to pinpoint unsatisfactory aspects of the reader's relationships with colleagues, bosses, students and clients.
Keywords: Social psychology